Morphological dimension of the permanent dentition in various malocclusion: a systematic review and meta-analysis - Jerome Thomas; Annapurna Kannan; Vignesh Kailasam (BMC Oral Health)
Abstract Background Achieving optimal dentofacial aesthetics requires an understanding of tooth morphology and its impact on dental harmony. Variations in tooth size can significantly influence the occurrence of different malocclusions, affecting aesthetics and functional occlusion. This systematic review aims to analyse and summarise the existing literature on tooth size variations in different malocclusion categories, focusing on the morphological dimensions of permanent dentition. Methods Systematic literature search was conducted in six electronic databases (PubMed/Medline, Cochrane, Web of science, Scopus, LILAC, OVID) until February 2025 for original articles assessing the morphological dimension of the permanent dentition in various malocclusions. The risk of bias and quality assessment was done using the modified Downs and Black quality index for retrospective and cross sectional study. The review was registered on Prospero (CRD42024526671). Results Nine studies (4 retrospective, 5 cross sectional) met the eligibility criteria. A total of 2044 pre-treatment dental casts of patients with various malocclusions were included. In mandibular first molars, the mean difference (MD) of the mesiodistal width was higher in Class III malocclusion than Class II div 1 malocclusion (3 studies; MD [95%CI]: 0.45[, -0.66, -0.24]), Class II division 2 malocclusion (3 studies; MD [95%CI]: 0.29[, -0.55, -0.24]) and Class I malocclusion (7 studies; MD [95%CI]: 0.20[ -0.35 to -0.05]). These findings were statistically significant. For mandibular canines, MD of the mesiodistal width was higher in Class III malocclusion than in Class II division 1 malocclusion (3 studies; MD [95%CI]:0.28 [ -0.45 to -0.10]), which was statistically significant. With the maxillary canines, the MD of the mesiodistal width was higher in Class II division 1 malocclusion (3 studies; MD [95%CI]: 0.30[0.12, 0.47]), which was statistically significant. Conclusion In Class III malocclusion, the mandibular dentition was found to be significantly larger compared to other malocclusions. The Maxillary dentition was significantly larger in Class II malocclusion compared to other malocclusions. Within the limitations of the study, Class III and Class II malocclusions were found to have larger mesio-distal width as compared to Class I malocclusion. These findings may aid clinicians in treatment planning, particularly in space analysis, arch coordination, and appliance selection during orthodontic interventions.